ANALISIS PENGARUH KEBERAGAMAN DEWAN DIREKSI TERHADAP KEMUNGKINAN FINANCIAL DISTRESS DENGAN ROA DAN FIRM SIZE SEBAGAI VARIABEL KONTROL (Studi Kasus pada Bank Umum yang Terdaftar di BEI pada Tahun 2016-2020) - Dahniar Fara Fatima; Harjum Muharam; Danes Quirira Octavio (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze the relationship between the board of director diversity and financial distress. This research used board of director size, gender diversity, age diversity, and nationality diversity as the independent variable, while financial distress measured with Altman Z-Score was adopted as the dependent variable. This research also implemented control variables using ROA and firm size. The sample used in this study is conventional bank listed on Indonesia Stock Exchange in 2016-2020. A total of 36 conventional banks were used as the sample obtained using the purposive sampling method. The analytical method used in this research is binomial logistic regression analysis using IBM SPSS 25. The result of this study discovered that board of director size has a negative significant effect on financial distress. Meanwhile, gender, age, and nationality diversity does not affect financial distress. The score of Nagelkerke R-Square is 29,1% which means there are 70,9% of factors not included in this research that affect the possibilities of financial distress